Late Jurassic to Early Cretaceous age of the Daqiao gold deposit, West Qinling Orogen, China: implications for regional metallogeny - Wu, Y.; Li, J.; Evans, Katy; Vasconcelos, P.; Thiede, D.; Fougerouse, Denis; Rempel, Kirsten (Springer, 2018)
The West Qinling Orogen is endowed with more than 100 sediment-hosted gold deposits with an estimated resource of > 2000 t Au. Previous radiometric dating results have shown that most deposits formed during a Late Triassic to Early Jurassic period of contractional deformation over the orogen. However, here we show that the newly discovered Daqiao gold deposit (> 105 t at 3–4 g/t) in the southern belt of the West Qinling Orogen formed in latest Jurassic to Early Cretaceous under a different tectonic regime. The Daqiao gold deposit is hosted in weakly metamorphosed Triassic turbidites and is spatially associated with hydrothermally altered granodiorite and diorite porphyry dykes. Six granodiorite dykes have similar zircon U–Pb ages ranging from 215.0 ± 1.1 to 211.5 ± 1.5 Ma (1s), whereas one diorite porphyry dyke has a zircon U–Pb age of 187.5 ± 2.1 Ma (1s). The age of gold mineralization is constrained by two types of sericite: sericite aggregates coexisting with disseminated auriferous pyrite in relatively high-grade breccia ores and sericite coexisting with auriferous pyrite in weakly mineralized granodiorite dykes. Sericite aggregates from the breccia ores have 40Ar/39Ar plateau ages ranging from 150.7 ± 3.1 to 142.3 ± 2.5 Ma (2s), whereas grains from the altered granodiorite dykes and low-grade breccia ores have 40Ar/39Ar plateau ages of 130.8 ± 3.1 to 127.2 ± 0.6 Ma (2s). The 40Ar/39Ar ages thus suggest two periods of gold mineralization in the latest Jurassic and Early Jurassic that are likely related to repeated brecciation at Daqiao. These Jurassic-Cretaceous mineralization ages coincide with discounted ages from several other gold deposits in the region and suggest that there is an underappreciated gold event in the West Qinling Orogen that may not have been associated with the orogenic deformation but is genetically related to the far-field effects of plate reorganization during Paleo-Pacific subduction beneath the eastern Eurasian continent.